Formation of public opinion with KGB methods: discreditation and desinformation - Brinskaitė, Kristina (Genocidas ir rezistencija, 2006)
From the XX century sixties KGB in a struggle with antisoviet resistance besides physical repressions started to used methods of psychological impact. For KGB it was very important not only su supress opponents, but also to show to society their activity from negative perspective, to reduce numbers of supporters, justify repression against them. Discreditation and dissinformatin were one of the main methods in a struggle with inner and outside anemies
Keywords: KGB; repressive structures; KGB methods; propaganda; discreditation; disinformation